Hieracium racemosum subsp. lucanum (Asteraceae), a new hawkweed from southern Italy - Di Gristina, Emilio; Domina, Gianniantonio; Gottschlich, Günter; Maturo, Francesco; Scafidi, Filippo (Phytotaxa, 2019)
A new endemic taxon of Hieracium belonging to the H. racemosum aggregate is described from Basilicata (southern Italy) and named H. racemosum subsp. lucanum. Information on its morphology, distribution, ecology and taxonomic relationship is provided.